2014
DOI: 10.1002/bmc.3241
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid and geniposide in rat plasma by UPLC‐MS/MS and its application to a pharmacokinetic study after administration of Reduning injection

Abstract: A simple, specific and sensitive ultra-performance liquid chromatography tandem mass spectrometry (UPLC-MS/MS) method was established and validated for simultaneous determination of neochlorogenic acid, chlorogenic acid, cryptochlorogenic acid and geniposide in rat plasma using puerarin as an internal standard (IS). Plasma samples were pretreated by a one-step direct protein precipitation procedure with acetonitrile after acidified using as little as 50 μL plasma. Chromatographic separation was performed on an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 13 publications
3
18
0
Order By: Relevance
“…Identification and 119.22 ± 2.66 e quantitation of phenolic acids was carried out by comparison of the obtained retention time peaks of the examined samples with the retention time of the corresponding standards and by using obtained calibration curves for each standard. The 3-and 4-caffeoylquinic acids were collected in the end of the HPLC capillary and identified by mass spectrometer as was described by Wang et al [35]. The 3-and 4-caffeoylquinic acids and other unidentified phenolic acids were quantified as 5-caffeoylquinic acid (chlorogenic acid).…”
Section: Isolation and Determination Of Phenolic Acids (Pa) From Cbmentioning
confidence: 99%
“…Identification and 119.22 ± 2.66 e quantitation of phenolic acids was carried out by comparison of the obtained retention time peaks of the examined samples with the retention time of the corresponding standards and by using obtained calibration curves for each standard. The 3-and 4-caffeoylquinic acids were collected in the end of the HPLC capillary and identified by mass spectrometer as was described by Wang et al [35]. The 3-and 4-caffeoylquinic acids and other unidentified phenolic acids were quantified as 5-caffeoylquinic acid (chlorogenic acid).…”
Section: Isolation and Determination Of Phenolic Acids (Pa) From Cbmentioning
confidence: 99%
“…Various chromatographic methods have been published for the determination of GE or GP in combination with other compounds in the biological matrix using HPLC‐UV or LC–MS/MS (Chen et al, ; Cheng, Lin, Lin, & Tsai, ; He et al, ; Hu et al, ; Huang et al, ; Peng et al, ; Qu et al, , ; Wang et al, ). Some methods have been established for simultaneous quantification of GE and GP.…”
Section: Introductionmentioning
confidence: 99%
“…The underlying mechanism is normally not clear . It was reported that polyphenol compounds and iridoids were the main components in RDN, including Chlorogenic Acid, Caffeic Acid, Isochlorogenic Acid B, Isochlorogenic Acid A, Isochlorogenic Acid C,Geniposide and so on (Wang et al, 2014;Zhang et al, 2014). Recent studies demonstrated that Chlorogenic Acid, Isochlorogenic Acid A, Isochlorogenic Acid B and Isochlorogenic Acid C could attenuate the release of PGE 2 and IL-6 in macrophage Shan et al, 2009).…”
Section: Discussionmentioning
confidence: 97%